Expeditious one-pot three component synthesis of N-aryl dithiocarbamate derivatives using mesoporous Cu-materials. Issue 13 (25th March 2015) - Payra, Soumen; Saha, Arijit; Peng, Rui; Wu, Chia-Ming; Koodali, Ranjit T.; Banerjee, Subhash
Graphical abstract: Abstract: In this study, a facile one-pot three component protocol has been demonstrated for the preparation of synthetically challenging N -aryl dithiocarbamate derivatives using mesoporous Cu-materials as catalyst at room temperature. The mesoporous Cu-catalysts namely Cu-MCM-41, Cu-MCM-48, and Cu-SBA-15 were prepared by impregnation of Cu-salts on the synthesized mesoporous materials and were characterized by powder X-ray diffraction, N2 adsorption–desorption, and transmission electron microscopic studies. Significant improvement of yields was obtained using mesoporous Cu-catalysts under milder reaction conditions compared to the earlier reported catalysts. All the three mesoporous Cu-catalysts showed comparative reactivity however a little higher yield was obtained using Cu-MCM-48.